A Comparison of Teacher-directed and Author-directed Peer Review in a Japanese University EFL Class - Matthew Coomber (Lecturer Association of Linguistics, Language Teaching, and Literature Studies in Indonesi, 2020)
Peer review is widely-used in EFL writing classes, and it has been found that students hold generally positive attitudes towards both providing and receiving peer feedback. However, while it is common for teachers to utilize peer response worksheets, little research has looked at the impact that the specific style of these sheets can have on how language learners conduct peer review and their attitudes towards it. In this study, participants first used a generic peer response sheet designed by the teacher (teacher-directed peer review), then an individualized peer response sheet that each learner had created, focusing on specific points that they wanted advice on (author-directed peer review). Surveys were conducted after each peer review session, and the data revealed that the two peer review styles prompted peer reviewers to give different types of feedback, with a greater focus on surface level issues during author-directed peer review. Furthermore, although all students agreed that both styles had been useful, 60% stated a preference for the author-directed style.